Development of redox-responsive theranostic nanoparticles for near-infrared fluorescence imaging-guided photodynamic/chemotherapy of tumor - Xiaoye Yang; Xiaoqun Shi; Jianbo Ji; Guangxi Zhai (Taylor & Francis Group, 2018)
The development of imaging-guided smart drug delivery systems for combinational photodynamic/chemotherapy of the tumor has become highly demanded in oncology. Herein, redox-responsive theranostic polymeric nanoparticles (NPs) were fabricated innovatively using low molecular weight heparin (LWMH) as the backbone. Chlorin e6 (Ce6) and alpha-tocopherol succinate (TOS) were conjugated to LMWH via cystamine as the redox-sensitive linker, forming amphiphilic Ce6-LMWH-TOS (CHT) polymer, which could self-assemble into NPs in water and encapsulate paclitaxel (PTX) inside the inner core (PTX/CHT NPs). The enhanced near-infrared (NIR) fluorescence intensity and reactive oxygen species (ROS) generation of Ce6 were observed in a reductive environment, suggesting the cystamine-switched "ON/OFF" of Ce6. Also, the in vitro release of PTX exhibited a redox-triggered profile. MCF-7 cells showed a dramatically higher uptake of Ce6 delivered by CHT NPs compared with free Ce6. The improved therapeutic effect of PTX/CHT NPs compared with mono-photodynamic or mono-chemotherapy was observed in vitro via MTT and apoptosis assays. Also, the PTX/CHT NPs exhibited a significantly better in anti-tumor efficiency upon NIR irradiation according to the results of in vivo combination therapy conducted on 4T1-tumor-bearing mice. The in vivo NIR fluorescence capacity of CHT NPs was also evaluated in tumor-bearing nude mice, implying that the CHT NPs could enhance the accumulation and retention of Ce6 in tumor foci compared with free Ce6. Interestingly, the anti-metastasis activity of CHT NPs was observed against MCF-7 cells by a wound healing assay, which was comparable to LMWH, suggesting LMWH was promising for construction of nanocarriers for cancer management.